Sistem Informasi Geografis Tour Dan Travel Berbasis Android Di Kabupaten Tegal - Farijz Milzan; Rinta Kridalukmana; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2016)
The development of a device move technology , facilitate human life in undergo kesehariannya .To progress , technology device move could determine the existence of users , find out which address want to intended , and give a route to the location .The use of devices movement for the district government tegal , and students tegal in particular made them in the visits to the agent travel and tourism tegal spread across the country .Needed a system that help you in seeking information on travel agent and tourist tegal especially for students and the tegal problems that hampered by the agent the location. The geographic information system created using the Java programming language with SDK (Software Development Kit) Android and using MySQL and SQLite databases, the system is a client-server. The process of making and development of Geographic Information System using SDLC (Software Development Life Cycle) using prototyping life cycle. By using the life cycle of prototyping, the design can be quickly created and tested by users. Users can participate in helping the development of a system to provide feedback on the prototype that has been tried before, so that the system be made better. The result of design this program is a system for the geographic information on device move that would facilitate users in find information and to travel agent and tourist attractions contained in district tegal .Information systems geographical location use technology LBS ( location based service ) , this technology allows users to find the location of travel agent and tourist destinations want to visited .This system will developed in a move that runs the android operating system.